All-solid-state battery
By setting more than 60% of the adhesive vertical orientation in the positive electrode active material layer of the all-solid lithium secondary battery, the problem of insufficient strength of the positive electrode active material layer is solved, and the balance between high energy density and output density is achieved.
Patent Information
- Application Number
- CN202280096139.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-19
- Publication Date
- 2024-12-31
AI Technical Summary
In the existing all-solid lithium secondary batteries, the outer peripheral end strength of the positive electrode active material layer is insufficient, and increasing the adhesive content will lead to a decrease in energy density and output density.
By setting the orientation ratio of the adhesive to 60% or more in the positive electrode active material layer, the vertical orientation of the adhesive in the lamination direction is ensured, the strength of the positive electrode active material layer is enhanced, and the adhesive content is reduced to maintain a high energy density .
The strength of the positive electrode active material layer is effectively improved, preventing short-circuit failures and output reduction, while maintaining high energy density and output density.
Smart Images

Figure BDA0005135916150000241 
Figure HDA0005135916160000011 
Figure HDA0005135916160000012
Abstract
Description
Technical Field
[0001] The invention relates to an all-solid-state battery. Background Art
[0002] In recent years, in order to cope with global warming, the reduction of carbon dioxide emissions has been urgently sought. In the automotive industry, there is a great expectation that the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs) will reduce carbon dioxide emissions, and the development of all-solid-state batteries such as secondary batteries for motor drives, which are the key to their practical application, is gaining momentum.
[0003] Secondary batteries for motor driving are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy among all batteries, have attracted attention and their development is being rapidly promoted.
[0004] Here, currently, the lithium secondary battery that is generally used uses a flammable organic electrolyte as an electrolyte. Such liquid lithium secondary batteries require stricter safety measures against leakage, short circuit, overcharge, etc. than other batteries.
[0005] Therefore, in recent years, research and development of all-solid-state secondary batteries using oxide-based and sulfide-based solid electrolytes in electrolytes has become popular. Solid electrolytes are materials mainly composed of ion conductors that can conduct ions in solids. Therefore, in principle, all-solid-state secondary batteries do not have various problems caused by flammable organic electrolytes such as previous liquid lithium secondary batteries. In addition, if high-potential / large-capacity positive electrode materials and large-capacity negative electrode materials are usually used, the output density and energy density of the battery can be greatly improved.
[0006] However, in all-solid-state secondary batteries, the positive electrode active material layer constituting part of the battery is known to be relatively brittle and may cause failures such as short circuits. In response to this, for example, Japanese Patent Publication No. 2019-021459 discloses a method for stably manufacturing a positive electrode active material layer by including a binder in the positive electrode active material layer. Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, the inventors found during the study that the strength of the outer peripheral end of the positive electrode active material layer was not fully improved in the positive electrode active material layer described in Japanese Patent Publication No. 2019-021459. On the other hand, it was found that in order to fully improve the strength, if the content of the binder in the positive electrode active material layer is increased, there is a problem of reducing energy density and reducing energy output.
[0009] Therefore, an object of the present invention is to provide a means for minimizing a decrease in energy density and energy output in an all-solid-state battery having a positive electrode active material layer including a binder, and for improving the strength of the positive electrode active material layer.
[0010] Solutions for solving problems
[0011] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by setting the orientation ratio of the binder contained in the positive electrode active material layer to a certain level or more, thereby completing the present invention.
[0012] An all-solid-state battery according to one embodiment of the present invention has a power generation element, the power generation element comprising: a positive electrode comprising a positive electrode active material layer comprising a positive electrode active material and a binder; a negative electrode; and a solid electrolyte layer, which is sandwiched between the positive electrode and the negative electrode and contains a solid electrolyte. Furthermore, the all-solid-state battery is characterized in that the orientation rate of the binder contained in the positive electrode active material layer in a direction perpendicular to the stacking direction of the power generation element is 60% or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a perspective view showing the appearance of a stacked battery according to one embodiment of the present invention.
[0014] Figure 2 For along Figure 1 A cross-sectional view along line 2-2 is shown.
[0015] Figure 3 To constitute Figure 1 and Figure 2 This is a schematic diagram showing an enlarged cross section of a single cell layer of a power generation element of a stacked battery.
[0016] Figure 4 This is a diagram for explaining a method for calculating the aspect ratio of a binder.
[0017] Figure 5 This is a schematic diagram showing an example of a branched fibrous binder.
[0018] Figure 6 This is a diagram schematically showing an example of a forming step in one embodiment of a method for producing a positive electrode active material layer. DETAILED DESCRIPTION
[0019] One embodiment of the present invention is an all-solid-state battery having a power generation element, the power generation element comprising: a positive electrode, which comprises a positive electrode active material layer containing a positive electrode active material and a binder; a negative electrode; and a solid electrolyte layer, which is sandwiched between the positive electrode and the negative electrode and contains a solid electrolyte, and the orientation rate of the binder contained in the positive electrode active material layer in a direction perpendicular to the stacking direction of the power generation element is 60% or more. According to the present invention, in an all-solid-state battery having a positive electrode active material layer containing a binder, the reduction in energy density and the reduction in energy output can be suppressed to a minimum, and the strength of the positive electrode active material layer can be improved.
[0020] Hereinafter, the embodiments of the present invention described above will be described with reference to the accompanying drawings, but the technical scope of the present invention shall be determined based on the description of the claims and shall not be limited to the following methods. It should be noted that the dimensional ratios of the accompanying drawings are sometimes exaggerated for the sake of convenience and are different from the actual ratios. Hereinafter, the present invention will be described by taking a non-bipolar (internal parallel) and flat stacked all-solid-state secondary battery (hereinafter also referred to as "stacked battery" or "all-solid-state battery") as an example of an all-solid-state battery. As described above, the solid electrolyte constituting the all-solid-state secondary battery is a material mainly composed of an ion conductor capable of ion conduction in a solid. Therefore, the all-solid-state secondary battery has the following advantages: in principle, various problems caused by flammable organic electrolytes such as those of previous liquid lithium secondary batteries do not occur. In addition, there are also the following advantages: usually, if a high potential / large capacity positive electrode material and a large capacity negative electrode material are used, a substantial improvement in the output density and energy density of the battery can be sought.
[0021] Figure 1 It is a perspective view showing the appearance of a stacked battery according to one embodiment of the present invention. Figure 2 For along Figure 1 The cross-sectional view of the line 2-2 shown in FIG. By making the battery into a stacked type, the battery can be made smaller and have a higher capacity.
[0022] like Figure 1 As shown, the stacked battery 10a has a rectangular flat shape, and a positive electrode collector plate 27 and a negative electrode collector plate 25 for outputting power are led out from both sides thereof. The power generation element 21 is surrounded by the battery outer packaging material (laminated film 29) of the stacked battery 10a, and its periphery is heat-welded, and the power generation element 21 is sealed in a state where the positive electrode collector plate 27 and the negative electrode collector plate 25 are led out to the outside.
[0023] In addition, about Figure 1There is no particular restriction on the removal of the collector plates (27, 25) shown. The positive collector plate 27 and the negative collector plate 25 may be led out from the same side, or the positive collector plate 27 and the negative collector plate 25 may be divided into multiple pieces and led out from each side, etc. Figure 1 As shown.
[0024] like Figure 2 As shown, in the stacked battery 10a of the present embodiment, the flat, roughly rectangular power generation element 21 that actually performs the charge and discharge reaction has a structure that is enclosed inside the battery outer packaging material, namely, a laminate film 29. Here, the power generation element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are stacked. The positive electrode has a structure in which a positive electrode active material layer 15 containing a positive electrode active material is arranged on both sides of a positive electrode collector 11". The negative electrode has a structure in which a negative electrode active material layer 13 containing a negative electrode active material is arranged on both sides of a negative electrode collector 11'. Specifically, one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 are placed opposite to each other with a solid electrolyte layer 17 in between, and the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order. Thus, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute a single battery layer 19. Therefore, Figure 1 The stacked battery 10 a shown has a structure in which a plurality of single cell layers 19 are stacked and connected electrically in parallel.
[0025] The positive electrode collector 11" and the negative electrode collector 11' are respectively installed with a positive electrode collector plate (pole tab) 27 and a negative electrode collector plate (pole tab) 25 that are conductive to each electrode (positive electrode and negative electrode), and have a structure in which they are led out to the outside of the laminate film 29 in a manner clamped by the end of the battery outer packaging material, i.e., the laminate film 29. The positive electrode collector plate 27 and the negative electrode collector plate 25 can each be installed on the positive electrode collector 11" and the negative electrode collector 11' of each electrode through ultrasonic welding, resistance welding, etc. via a positive electrode lead and a negative electrode lead (not shown) as needed.
[0026] Figure 3 To constitute Figure 1 and Figure 2 FIG. 1 is a schematic diagram showing an enlarged cross-section of a single cell layer 19 of a power generation element 21 of a stacked battery 10a. Figure 3 As shown, the single cell layer 19 of the present embodiment is a stack of a negative electrode collector 11', a negative electrode active material layer 13, a solid electrolyte layer 17, a positive electrode active material layer 15, and a positive electrode collector 11" which are stacked in sequence. In addition, the positive electrode active material layer 15 contains a binder 30, and the orientation rate of the binder in the direction perpendicular to the stacking direction of the power generation element (the direction of the arrow in the figure) is greater than 60%. It should be noted that the details of the "orientation rate of the binder" will be described later.
[0027] Hereinafter, main components of the all-solid-state secondary battery of this embodiment will be described.
[0028] [Current Collector]
[0029] The current collector has the function of mediating the movement of electrons from the electrode active material layer. The material constituting the current collector is not particularly limited. As the constituent material of the current collector, for example, metals and conductive resins can be used.
[0030] Specifically, as metal, aluminum, nickel, iron, stainless steel, titanium, copper, etc. can be cited. In addition, cladding materials of nickel and aluminum, cladding materials of copper and nickel, etc. can also be used. In addition, it can also be a foil formed by coating the metal surface with aluminum. Among them, from the viewpoints of electronic conductivity, battery operating potential, and adhesion of the negative electrode active material sputtered on the collector, aluminum, stainless steel, copper, and nickel are preferred.
[0031] Examples of the resin having conductivity include conductive polymer materials and resins obtained by adding conductive fillers to non-conductive polymer materials.
[0032] The conductive filler can be used without particular limitation as long as it is a material having conductivity. For example, examples of materials having excellent conductivity, potential resistance, or lithium ion shielding properties include metals and conductive carbon.
[0033] It should be noted that the current collector may be a single-layer structure formed by a single material, or may be a laminated structure formed by appropriately combining layers formed by these materials. From the perspective of lightweighting the current collector, it is preferred to include at least a conductive resin layer formed by a conductive resin. In addition, from the perspective of shielding the movement of lithium ions between single cell layers, a metal layer may be provided on a portion of the current collector.
[0034] [Positive electrode active material layer]
[0035] The positive electrode active material layer of this embodiment contains a positive electrode active material and a binder.
[0036] (Positive electrode active material)
[0037] There are no particular restrictions on the type of positive electrode active material, and examples thereof include layered rock salt active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 O4 and other spinel active materials, LiFePO4, LiMnPO4 and other olivine active materials, Li2FeSiO4, Li2MnSiO4 and other Si-containing active materials, etc. In addition, examples of oxide active materials other than the above include Li4Ti5O12 . Among them, it is preferred to use a composite oxide containing lithium and nickel, and it is further preferred to use Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter also simply referred to as "NMC composite oxide"). NMC composite oxide has a layered crystal structure in which lithium atomic layers and transition metal (Mn, Ni and Co are regularly arranged) atomic layers are alternately stacked via oxygen atomic layers. It contains 1 Li atom for every 1 atom of transition metal M, and the amount of Li extracted is twice that of spinel lithium manganese oxide, that is, the supply capacity is doubled, and it can have a high capacity.
[0038] As described above, NMC composite oxides also include composite oxides in which a part of transition metal elements is replaced by other metal elements. As other elements in this case, Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc. can be listed, preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and from the viewpoint of improving cycle characteristics, Ti, Zr, Al, Mg, Cr are further preferably.
[0039] Furthermore, the use of a sulfur-based positive electrode active material is also one of the preferred embodiments. Examples of the sulfur-based positive electrode active material include particles or films of organic sulfur compounds or inorganic sulfur compounds, which can release lithium ions during charging and absorb lithium ions during discharging by utilizing the redox reaction of sulfur.
[0040] Depending on the situation, two or more positive electrode active materials may be used in combination. It should be noted that, of course, positive electrode active materials other than the above may also be used. The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, for example, preferably in the range of 35 to 99 mass %, more preferably in the range of 40 to 90 mass %.
[0041] (Adhesive)
[0042] The positive electrode active material layer of this embodiment contains a binder, and the orientation rate of the binder in the direction perpendicular to the stacking direction of the power generation element (also referred to as the "surface direction") is 60% or more. According to the all-solid-state battery of this embodiment, by making the orientation rate of the binder in the positive electrode active material layer in the surface direction 60% or more, the reduction in energy density and output can be suppressed to a minimum, and the strength of the positive electrode active material layer can be improved.
[0043] The mechanism for producing the above-mentioned effect is not completely clear, but it is speculated as follows. That is, by configuring the binder in a manner of being oriented in the face direction, even if an external force (e.g., compressive stress, bending stress) is applied to the positive electrode active material layer from the stacking direction, an internal force that can resist it can also be generated, and as a result, the strength of the positive electrode active material layer becomes sufficient. Similarly, even when an external force (e.g., tensile stress, shear stress) is applied to the positive electrode active material layer from the face direction, by configuring the binder in the above manner, an internal force that can resist the external force can also be generated, and as a result, the strength of the positive electrode active material layer becomes sufficient. It is therefore believed that when the all-solid-state battery repeatedly expands and contracts due to charging and discharging, cracks and collapses in the positive electrode active material layer caused by external forces also become less likely to occur, thereby preventing the output of the all-solid-state battery from being reduced.
[0044] In addition, as a method for improving the strength of the positive electrode active material layer, it is considered to increase the content of the binder contained in the positive electrode active material layer, but in this case, the energy density of the all-solid-state battery will be reduced. In the positive electrode active material layer of this method, the binder is arranged in a manner oriented in the plane direction, based on the above mechanism, so that sufficient strength can be ensured and the content of the binder can be reduced. Thus, even if the content of the binder is small, sufficient strength can be ensured, and an all-solid-state battery with high energy density can be obtained.
[0045] In the secondary battery of this embodiment, the orientation ratio of the binder in the positive electrode active material layer can be calculated as follows.
[0046] First, the configuration state of the binder in the cross section of the positive electrode active material layer parallel to the stacking direction of the power generation element is determined. The configuration state of the binder can be determined by observing the cross section through SEM-EDX and mapping the elements unique to the binder. It should be noted that if the same results as SEM-EDX can be obtained, AES (Auger electron spectroscopy), EPMA (electron probe microanalyzer), etc. can also be used to map the binder in the cross section.
[0047] Next, the average value of the aspect ratio of the binder is calculated from the configuration state of each binder in the cross section of the positive electrode active material layer. The average value of the aspect ratio of the binder is calculated as follows: First, 100 or more binders are taken from all the binders included in the cross-sectional observation image.
[0048] Next, the aspect ratio of each adhesive removed is calculated. Specifically, in the above-mentioned observation image, if Figure 4 As shown, it is set to have sides (longitudinal sides, Figure 4 H) and vertical sides (horizontal sides, Figure 4 W) of the rectangle ( Figure 4The adhesive 30 is inscribed in the rectangle shown by the dotted line in FIG. Then, the value obtained by dividing the length of the horizontal side of the rectangle by the length of the vertical side is calculated as the aspect ratio (1 / tanθ). Then, the average value of the aspect ratios of the adhesives taken out is calculated and set as the average value of the aspect ratios of the adhesives (1 / tanθ).
[0049] Next, θ[°] was calculated from the calculated average value of the aspect ratios (1 / tanθ). Then, from the value of θ, a value calculated based on the following formula 1 was calculated as the orientation ratio (%) of the binder in the positive electrode active material layer.
[0050] Orientation rate (%) = (1-θ / 90) × 100… (Formula 1)
[0051] Since the binder is considered to be uniformly dispersed in the positive electrode active material layer, the orientation ratio calculated by observing at least one cross section of the positive electrode active material layer can be regarded as the orientation ratio of the binder in the entire positive electrode active material layer.
[0052] The lower limit of the orientation rate of the binder in the positive electrode active material layer of this embodiment is 60% or more, preferably 65% or more, more preferably 70% or more, further preferably 75% or more, particularly preferably 80% or more, and most preferably 85% or more. By setting the orientation rate of the binder to this range, when an external force (such as compressive stress and bending stress) is applied to the positive electrode active material layer from the stacking direction, the strength of the positive electrode active material layer can be made more sufficient. In addition, the upper limit of the orientation rate of the binder of this embodiment is preferably 90% or less. By setting the orientation rate of the binder to this range, when an external force (such as tensile stress and shear stress) is applied from a direction perpendicular to the stacking direction, the positive electrode active material layer can exert sufficient internal force. That is, the orientation rate of the adhesive of this embodiment is preferably 60% to 90%, more preferably 65% to 90%, further preferably 70% to 90%, further preferably 75% to 90%, particularly preferably 80% to 90%, and most preferably 85% to 90%.
[0053] Relative to the gross mass of the positive active material layer, the upper limit of the content of the binder in the positive active material layer of the present mode is preferably 3.2% by mass or less, more preferably 3.1% by mass or less, and further preferably 3.0% by mass or less. By making the content of the binder the range, the energy density and energy output of the all-solid-state battery become sufficiently high. On the other hand, the lower limit of the content of the binder in the positive active material layer of the present mode is preferably 0.6% by mass or more, more preferably 0.7% by mass or more, further preferably 0.8% by mass or more, particularly preferably 1.0% by mass or more, and most preferably 1.5% by mass. By making the content of the binder the range, the strength of the positive active material layer can be made more sufficient. That is, relative to the total mass of the positive electrode active material layer, the content of the binder in the positive electrode active material layer of the present embodiment is preferably greater than 0.6 mass % and less than 3.2 mass %, more preferably greater than 0.7 mass % and less than 3.1 mass %, further preferably greater than 0.8 mass % and less than 3.0 mass %, particularly preferably greater than 1.0 mass % and less than 3.0 mass %, and most preferably greater than 1.5 mass % and less than 3.0 mass %.
[0054] The binder is not particularly limited, and examples thereof include the following.
[0055] Examples include: thermoplastic polymers such as polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated product, styrene-isoprene-styrene block copolymer and its hydrogenated product, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene Fluororesins such as (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene fluororubber (VDF-HFP fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene fluororubber (VDF-HFP-TFE fluororubber), vinylidene fluoride-pentafluoropropylene fluororubber (VDF-PFP fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene fluororubber (VDF-PFP-TFE fluororubber), vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene fluororubber (VDF-PFMVE-TFE fluororubber), vinylidene fluoride-chlorotrifluoroethylene fluororubber (VDF-CTFE fluororubber), etc., epoxy resins, etc. Among them, from the viewpoint that the strength of the positive electrode active material layer can be more sufficient by being entangled with other components, the binder preferably includes a fibrous binder. In this specification, "fibrous binder" refers to a binder mainly composed of fibers with an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less in the observation image when observing the cross section of the positive electrode active material layer using a scanning electron microscope (SEM). Here, the aspect ratio is calculated by dividing the maximum Feret diameter of the binder by the minimum Feret diameter. It should be noted that the maximum Feret diameter refers to the maximum distance between the straight lines when the contour of the binder is clamped by two parallel straight lines, and the minimum Feret diameter refers to the minimum distance between the straight lines when the contour of the binder is clamped by two parallel straight lines. The so-called binder "mainly composed of" the above-mentioned fibers means that the area ratio of the above-mentioned fiber part to the total area of the binder in the SEM observation image is 50% or more. A fibrous binder may include a portion other than the fiber with an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less (a portion with an aspect ratio of less than 10 or a portion with a minimum Feret diameter exceeding 0.2 μm).However, the area ratio of the portion other than the fibers in the SEM observation image to the total area of the fibrous adhesive needs to be less than 50%, preferably less than 20%, more preferably less than 10%, and further preferably less than 5% (the lower limit is 0%). Fibrous adhesives include not only adhesives consisting of only one fiber, but also adhesives having a structure in which two or more fibers are connected to each other. As specific shapes of adhesives having a structure in which two or more fibers are connected to each other, branched, radial, and mesh shapes, as well as shapes formed by combining them, can be listed. Here, the method for calculating the maximum Feret diameter and the minimum Feret diameter in an adhesive having a structure in which two or more fibers are connected to each other is explained. Figure 5 This is a schematic diagram showing an example of a branched fibrous binder. Figure 5 The adhesive 30 shown has a structure in which fibers X, Y, and Z are connected to each other. Each dotted line represents a line connecting the center of the width of the fibers (1 / 2 width), and points A, B, and C represent the ends of each dotted line. It should be noted that the ends of each dotted line coincide with the ends of the fibers. Point D represents the intersection of the three dotted lines. That is, Figure 5 The adhesive 30 shown can also be said to have a shape in which the fiber X from point A to point D, the fiber Y from point B to point D, and the fiber Z from point C to point D are bonded at point D. Figure 5 The maximum Feret's diameter of fiber X in the adhesive 30 shown is defined as the distance from point A to point D. Similarly, the maximum Feret's diameter of fiber Y is the distance from point B to point D, and the maximum Feret's diameter of fiber Z is the distance from point C to point D. In addition, the minimum Feret's diameter of fiber X is the minimum distance between two parallel straight lines when the contour of the adhesive (fiber) between points A and D is clamped by the straight lines. The same applies to the minimum Feret's diameters of fiber Y and fiber Z. Figure 5 In the adhesive 30 shown, the fibers Y and Z have an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less, but the aspect ratio of the fiber X is less than 10. However, since the area occupied by the fiber X portion in the total area of the adhesive 30 is less than 50%, it can be said that Figure 5The adhesive shown is a fibrous adhesive. As the type of fibrous adhesive, as long as it has the above-mentioned shape in the positive electrode active material layer, there is no particular restriction, and an adhesive that is fibrillated by applying shear force can be preferably used. As the type of such a fibrillated adhesive, nanofibers such as polytetrafluoroethylene (PTFE), carboxymethyl cellulose, polyvinyl alcohol, polyethylene, cellulose nanofibers, and Kevlar (Kevar, a registered trademark, polyparaphenylene terephthalamide) fibers are preferred, and polytetrafluoroethylene (PTFE) is more preferred. Fibrous adhesives can be used alone or in combination of two or more. It should be noted that in this specification, the record of the compound name of the adhesive can include not only the compound shown in the compound name, but also a form in which a part of the terminal or side chain is replaced (modified) by other substituents. In the case of a form in which a part of the terminal or side chain is replaced (modified) by other substituents, the proportion of the structural unit in which the terminal or side chain is replaced (modified) by other substituents in the structural unit of 100 mol% of all structural units is preferably 10 mol% or less, more preferably 5 mol% or less.
[0056] The length of the fibrous binder is preferably 5 to 50 μm, more preferably 8 to 15 μm. In addition, the diameter of the fibrous binder is preferably 20 to 500 nm, more preferably 50 to 200 nm. By making the size of the binder within such a range, the strength of the positive electrode active material layer becomes sufficient. It should be noted that the length and diameter of the fibrous binder are set to the average value of several to dozens of measurements using a transmission electron microscope (TEM) or a scanning electron microscope (SEM).
[0057] (Solid Electrolyte)
[0058] The positive electrode active material layer preferably further includes a solid electrolyte. By making the positive electrode active material layer include a solid electrolyte, the ion conductivity of the positive electrode active material layer can be improved. As solid electrolytes, for example, sulfide solid electrolytes and oxide solid electrolytes can be listed, but from the viewpoint of high ion conductivity, it is preferred to include a sulfide solid electrolyte. It should be noted that in this specification, a solid electrolyte refers to a material composed mainly of an ion conductor capable of ion conduction in a solid, and in particular refers to a material having a lithium ion conductivity of 1×10 at room temperature (25°C). -5 S / cm or more, the lithium ion conductivity is preferably 1×10 -4 Here, the value of ion conductivity can be measured by an AC impedance method.
[0059] As sulfide solid electrolytes, examples include: LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS 4、 Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is any of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In), etc. It should be noted that the description of "Li2S-P2S5" means a sulfide solid electrolyte formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0060] Sulfide solid electrolytes can, for example, have a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. As sulfide solid electrolytes having a Li3PS4 skeleton, examples include LiI-Li3PS4, LiI-LiBr-Li3PS 4、 Li3PS4. Additionally, as sulfide solid electrolytes having a Li4P2S7 skeleton, examples include Li-P-S-based solid electrolytes called LPS (e.g., Li7P3S 11 ). Additionally, as sulfide solid electrolytes, for example, Li (4-x) Ge (1-x) P x S4 (where 0 < x < 1) such as LGPS can be used. Among them, the sulfide solid electrolyte is preferably a sulfide solid electrolyte containing a P element, and the sulfide solid electrolyte is more preferably a material mainly composed of Li2S-P2S5. Furthermore, the sulfide solid electrolyte can also contain halogens (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (here, X is Cl, Br, or I, preferably Cl).
[0061] In addition, when the sulfide solid electrolyte is a Li2S-P2S5 system, the ratio of Li2S to P2S5 is preferably in the range of Li2S:P2S5=50:50 to 100:0 in terms of molar ratio, among which Li2S:P2S5=70:30 to 80:20 is preferred.
[0062] In addition, the sulfide solid electrolyte may be sulfide glass, crystallized sulfide glass, or a crystalline material obtained by a solid phase method. It should be noted that sulfide glass can be obtained, for example, by mechanically grinding (ball milling, etc.) the raw material composition. In addition, crystallized sulfide glass can be obtained, for example, by heat treating sulfide glass at a temperature above the crystallization temperature. In addition, the ion conductivity (for example, Li ion conductivity) of the sulfide solid electrolyte at room temperature (25°C) is preferably, for example, 1×10 -5 S / cm or more, more preferably 1×10 -4 S / cm or more. It should be noted that the value of the ion conductivity of the solid electrolyte can be measured by an alternating current impedance method.
[0063] As the shape of the solid electrolyte, for example, a true spherical, ellipsoidal, or other particle shape, a thin film shape, etc. can be cited. When the solid electrolyte is in a particle shape, its average particle size (D50) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less. On the other hand, the average particle size (D50) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.
[0064] The content of the solid electrolyte in the positive electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, more preferably in the range of 10 to 50 mass %.
[0065] (Conductive additive)
[0066] The positive electrode active material layer of this embodiment may contain a conductive aid. If the positive electrode active material layer contains a conductive aid, an electronic network inside the positive electrode active material layer can be efficiently formed, which can contribute to the improvement of the output characteristics of the battery. As conductive aids, for example, metals such as aluminum, stainless steel (SUS), silver, gold, copper, titanium, alloys or metal oxides containing these metals; carbon fibers (specifically, vapor deposited carbon fibers (VGCF), polyacrylonitrile carbon fibers, pitch carbon fibers, rayon carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), carbon black (specifically, acetylene black, Ketjen black (registered trademark), furnace black, channel black, hot lamp black, etc.) and other carbons can be cited, but are not limited to these. In addition, granular ceramic materials and those obtained by coating the above-mentioned metal materials around the resin material by plating or the like can also be used as conductive aids. Among these conductive aids, from the viewpoint of electrical stability, it is preferred to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium and carbon, more preferably at least one selected from the group consisting of aluminum, stainless steel, silver, gold and carbon, and further preferably at least one carbon. These conductive aids may be used alone or in combination of two or more. The electronic conductivity of the conductive aid is preferably 1 S / m or more, more preferably 1×10 2 S / m or more, more preferably 1×10 4 S / m or more, more preferably 1×10 5 S / m or more. The upper limit of the electronic conductivity of the conductive additive is not particularly limited, but is usually 1×10 7 S / m or less.
[0067] The shape of the conductive aid is not particularly limited, and is preferably fibrous or flat, and more preferably fibrous. By making the conductive aid in these shapes, the strength of the positive electrode active material layer becomes sufficient, and in particular, by making the conductive aid in a fibrous shape, the conductive aid is entangled with other components of the positive electrode active material layer, so that the strength of the positive electrode active material layer becomes more sufficient.
[0068] As the fibrous conductive additive, for example, there can be mentioned carbon fibers such as PAN-based carbon fibers and asphalt-based carbon fibers, conductive fibers obtained by uniformly dispersing metals and graphite having good conductivity in synthetic fibers, metal fibers obtained by fiberizing metals such as stainless steel, conductive fibers obtained by covering the surface of organic fibers with metals, conductive fibers obtained by covering the surface of organic fibers with resins containing conductive substances, etc. Among them, carbon fibers are preferred because of their excellent conductivity and light weight.
[0069] When the conductive aid is fibrous, its length is preferably 5 to 20 μm, more preferably 8 to 15 μm. In addition, when the conductive aid is fibrous, the diameter of the conductive aid is preferably 20 to 500 nm, more preferably 50 to 300 nm. By making the size of the conductive aid such a range, the strength of the positive electrode active material layer becomes more sufficient. It should be noted that the length and diameter of the fibrous conductive aid can be set to the average value of several to dozens of measurements using a transmission electron microscope (TEM) or a scanning electron microscope (SEM).
[0070] The shape of the conductive aid can be granular in addition to the fibrous shape. The shape of the particles is not particularly limited and can be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, flaky, spindle, etc. The average particle size (primary particle size) of the conductive aid in the granular state is not particularly limited, but from the perspective of the electrical properties of the battery, it is preferably 0.01 to 10 μm. It should be noted that in this specification, the "particle size of the conductive aid" refers to the maximum distance L between any two points on the contour line of the conductive aid. As the value of the "average particle size of the conductive aid", a value calculated as the average value of the particle size of the particles observed in several to dozens of fields of view using an observation method such as a scanning electron microscope (SEM) and a transmission electron microscope (TEM) can be used.
[0071] When the positive electrode active material layer includes a conductive auxiliary agent, the content of the conductive auxiliary agent in the positive electrode active material layer is not particularly limited, and is preferably 0 to 10% by mass, more preferably 1.0 to 8% by mass, and further preferably 2.0 to 5.0% by mass relative to the total mass of the positive electrode active material layer. If it is within such a range, a more stable electron conduction path can be formed in the positive electrode active material layer, which can efficiently contribute to the improvement of battery characteristics.
[0072] For the lower limit of the orientation rate of the conductive aid in the positive electrode active material layer of this embodiment in the direction perpendicular to the stacking direction of the power generation element (plane direction), it is preferably 55% or more in the plane direction, more preferably 60% or more, further preferably 65% or more, and particularly preferably 70% or more. By making the orientation rate of the conductive aid within the above range, the strength of the positive electrode active material layer becomes more sufficient. In addition, the upper limit of the orientation rate of the conductive aid in this embodiment is preferably 90% or less. By making the upper limit of the orientation rate of the conductive aid within this range, when an external force (such as tensile stress and shear stress) is applied to the positive electrode active material layer from the plane direction, the positive electrode active material layer can exert sufficient internal force. That is, the orientation rate of the conductive aid in this embodiment is preferably 55% or more and 90% or less, more preferably 60% or more and 90% or less, further preferably 65% or more and 90% or less, and particularly preferably 70% or more and 90% or less. It should be noted that the orientation rate of the conductive aid is calculated using the same method as the orientation rate of the aforementioned binder.
[0073] The thickness of the positive electrode active material layer varies depending on the configuration of the intended all-solid-state battery, but is preferably within a range of 0.1 to 1000 μm, and more preferably 40 to 100 μm, for example.
[0074] [Solid electrolyte layer]
[0075] The solid electrolyte layer contains a solid electrolyte as a main component and is a layer interposed between the negative electrode active material layer and the positive electrode active material layer. The specific form of the solid electrolyte contained in the solid electrolyte layer is the same as that described above, so detailed description is omitted here.
[0076] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass %, more preferably in the range of 50 to 100 mass %, and even more preferably in the range of 90 to 100 mass %.
[0077] The solid electrolyte layer may contain a binder in addition to the above-mentioned solid electrolyte. The specific form of the binder that may be contained in the solid electrolyte layer is the same as that described above, and thus detailed description thereof is omitted here.
[0078] The thickness of the solid electrolyte layer varies depending on the configuration of the target all-solid-state battery, but from the viewpoint of being able to improve the volume energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and further preferably 400 μm or less. On the other hand, the lower limit of the thickness of the solid electrolyte layer is not particularly limited, but is preferably 1 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more.
[0079] [Negative Electrode Active Material Layer]
[0080] The negative electrode active material layer contains a negative electrode active material. There is no particular limitation on the type of negative electrode active material, and carbon materials, metal oxides and metal active materials can be listed. In addition, as the negative electrode active material, a metal containing lithium can be used. Such a negative electrode active material is not particularly limited as long as it is an active material containing lithium. In addition to metallic lithium, lithium-containing alloys can also be listed. As lithium-containing alloys, for example, alloys of Li and at least one of In, Al, Si, Sn, Mg, Au, Ag and Zn can be listed. The negative electrode active material preferably contains metallic lithium or a lithium-containing alloy, a silicon-based negative electrode active material or a tin-based negative electrode active material, and particularly preferably contains metallic lithium or a lithium-containing alloy. It should be noted that when metallic lithium or a lithium-containing alloy is used as the negative electrode active material, the all-solid-state battery of this method can be a so-called lithium precipitation type in which lithium metal as a negative electrode active material is precipitated on the negative electrode collector during the charging process. Thus, in such a method, the thickness of the negative electrode active material layer increases with the progress of the charging process, and the thickness of the negative electrode active material layer decreases with the progress of the discharge process. The negative electrode active material layer may not exist during full discharge, but depending on circumstances, a certain amount of negative electrode active material layer composed of lithium metal may be disposed during full discharge.
[0081] On the other hand, when the all-solid-state battery is not a lithium precipitation type, the negative electrode active material layer is preferably the same as the above-mentioned positive electrode active material layer, and also includes a solid electrolyte, a binder and a conductive aid in addition to the negative electrode active material. Specific examples and preferred embodiments of these materials are as described in the positive electrode active material layer column.
[0082] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.
[0083] [Positive lead and negative lead]
[0084] In addition, although the figure is omitted, the collector and the collector plate can be electrically connected via a positive lead and a negative lead. As the constituent material of the positive and negative leads, the materials used in known lithium-ion secondary batteries can be used in the same manner. It should be noted that the portion taken out from the outer body is preferably covered with a heat-resistant insulating heat shrink tube, etc., so that it will not leak due to contact with surrounding equipment, wiring, etc., thereby affecting the product (such as automotive parts, particularly electronic equipment, etc.).
[0085] [Battery exterior materials]
[0086] As the battery outer material, a known metal can case can be used, and a Figure 1 and Figure 2 As shown, a bag-shaped case using a laminate film containing aluminum is used to cover the power generation element.
[0087] An embodiment of the all-solid-state battery has been described above, but the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0088] For example, in the all-solid-state battery of the present embodiment, the solid electrolyte layer may further include a liquid electrolyte (electrolyte) known in the past. The amount of the liquid electrolyte (electrolyte) that can be included in the solid electrolyte layer is not particularly limited, but is preferably an amount that maintains the shape of the solid electrolyte layer formed by the solid electrolyte and does not cause leakage of the liquid electrolyte (electrolyte).
[0089] [Method for manufacturing all-solid-state battery (positive electrode active material layer)]
[0090] The manufacturing method of the all-solid-state battery of this mode is not particularly limited. Here, an example of the method for making the positive electrode active material layer, which is the characteristic composition of the all-solid-state battery of this mode, is described. In this manufacturing method, first, a powder composition (positive electrode mixture) containing a positive electrode active material and a binder, and a solid electrolyte and a conductive aid as needed is prepared. Then, the powder composition (positive electrode mixture) is subjected to a rolling process by a roller press to prepare a positive electrode active material layer. That is, according to other modes of the present invention, a method for making a positive electrode active material layer of an all-solid-state battery of one mode of the present invention is also provided. The manufacturing method is characterized in that it has the following forming step: a powder composition (positive electrode mixture) containing a positive electrode active material and a binder (and a solid electrolyte and a conductive aid as needed) is supplied to a roller press, and the aforementioned powder composition is subjected to a roll rolling process more than 2 times using the aforementioned roller press to be formed into a sheet, thereby obtaining the aforementioned positive electrode active material layer.
[0091] It should be noted that in this specification, "roller press" refers to a machine having at least one pair of cylindrical pressure rollers and a rotating drive mechanism for the rollers, which sandwiches the powder composition (positive electrode mixture) between the pair of rollers and rolls it into a sheet, and the at least one pair of cylindrical pressure rollers is arranged so that the outer circumference faces are opposite and parallel. There are no special restrictions on the material and size of the rollers, the style of the rotating mechanism, and the configuration of the rollers and the rotating mechanism. In addition, the direction of discharging the positive electrode active material layer from between the pair of rollers is not particularly limited, and can be horizontal or downward.
[0092] Here, first, the powder composition (electrode mixture) used as a raw material in the above-mentioned manufacturing method is described. The powder composition needs to contain a positive electrode active material and a binder, and preferably further contains a solid electrolyte and a conductive aid. "Powder composition" refers to a mixture consisting of a solid component in a state that does not substantially contain liquid components such as solvents. It should be noted that, relative to 100% by mass of the powder composition, the content of the liquid component in the powder composition is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, more preferably 0.5% by mass or less, particularly preferably 0.1% by mass or less, and most preferably 0% by mass.
[0093] There is no particular restriction on the method for obtaining the powder composition, and the components constituting the powder composition can be added and mixed in any order. There is no particular restriction on the mixing means at this time, and a method using a mixing means such as a mortar, a mixer, a grinder, etc. known in the past can be appropriately adopted. Here, there is no particular restriction on the method of mixing the binder in the powder mixture, and the binder can be prepared separately and mixed with other components. In addition, when it is desired to include a fibrous binder in the powder mixture, when a precursor of the fibrous binder, i.e., a fibrillating binder, is mixed with other components, a shear force is applied to the fibrillating binder to fibrillate it, thereby generating a fibrous binder in the powder composition.
[0094] In the manufacturing method of this embodiment, a powder composition (positive electrode mixture) containing a positive electrode active material and a binder (and, if necessary, a solid electrolyte and a conductive aid) is supplied to a roller press, and the powder composition is rolled using the roller press to form a sheet. At this time, the powder composition is rolled twice or more using the roller press to form a sheet.
[0095] Figure 6 FIG. 1 is a diagram schematically showing an example of a forming step in one embodiment of a method for producing a positive electrode active material layer 15. Figure 6 As shown, in the forming process of the manufacturing method of this embodiment, the powder composition (positive electrode mixture) 100 is supplied to the roller press, and the powder composition (positive electrode mixture) 100 is rolled using the roller press (specifically, compressed by the roller 110 of the roller press) to form a sheet. The powder composition (positive electrode mixture) 100 formed into a sheet becomes the positive electrode active material layer 15, which is discharged in the horizontal direction and stacked on the surface of the substrate 200. It should be noted that the direction of discharging the powder composition (positive electrode mixture) formed into a sheet in the forming process is not particularly limited, for example, the positive electrode active material layer can be discharged in the vertical direction.
[0096] The substrate 200 may be moved in one direction according to the speed of forming the powder composition (positive electrode mixture) 100. The means for moving the substrate 200 in one direction is not particularly limited, but may be as follows: Figure 6 As shown in the figure, the substrate 200 is moved in one direction ( Figure 6 In addition, when the substrate 200 itself has sufficient mechanical strength, the substrate 200 may be moved in one direction by directly placing the substrate 20 on the driving portion 210b without providing the mounting portion 210a.
[0097] In the manufacturing method, the powder composition is subjected to roller rolling treatment for more than two times using a roller press to form a sheet. At this time, by appropriately adjusting the line pressure of the roller press, the number of rolling treatments, the speed of the roller and other conditions, a positive electrode active material layer for an all-solid-state battery of one embodiment of the present invention can be obtained.
[0098] The number of times the powder composition is rolled using a roller press is not easy to determine, but is preferably 4 to 10 times, more preferably 5 to 6 times. By setting the number of times the rolling treatment is performed within the above range, the orientation ratio of the binder (and thus the conductive additive) can be easily set to a desired value.
[0099] The linear pressure applied by the roller press to the powder composition is preferably 35 to 3500 N / cm. It should be noted that the linear pressure applied by the roller press to the powder composition refers to the linear pressure calculated based on the load obtained by the force sensor attached to the roller press and the electrode width after punching. The interval between the rollers of the roller press is not particularly limited, but from the perspective of the linear pressure applied to the powder composition and the perspective of adjusting the film thickness of the positive electrode active material layer, it is preferably 100 to 1000 μm. In addition, the rotation speed of the rollers of the roller press is not particularly limited, but from the perspective of ensuring sufficient punching holding time, it is preferably 1 to 20 m / min.
[0100] According to the manufacturing method of this embodiment, the positive electrode active material layer can be obtained by using a roller press to form a powder composition containing a positive electrode active material. Such a simple operation is not easy to cause forming errors and the yield is high. In addition, when the binder contained in the powder composition is formed, a shear force in the flow direction of the rolling can be applied. Such a rolling treatment is performed multiple times, and as a result, the binder (preferably a fibrous binder) having a random orientation in the state of the powder composition is oriented in a direction (plane direction) perpendicular to the stacking direction of the power generation element.
[0101] For the second and subsequent rolling treatments using a roller press, for example, the positive electrode active material layer obtained by rolling treatment once or more can be folded into a laminate, and the roller spacing of the roller press can be set in such a way that the thickness of the laminate becomes less than half the thickness. There is no particular limitation on the folding method of the positive electrode active material layer, and for example, folding in half, folding in three, folding in four, etc. can be cited.
[0102] It should be noted that, for an all-solid-state battery having a positive electrode active material layer manufactured as described above, it can be manufactured, for example, as follows. First, the positive electrode collector, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode collector are stacked in sequence, and a power generation element is obtained by pasting them by isostatic pressing or the like. Then, the positive electrode lead and the negative electrode lead are connected to the obtained power generation element, and the battery outer body such as an aluminum laminate film is loaded and vacuum-sealed. In this way, the all-solid-state battery of the present embodiment can be manufactured. It should be noted that a negative electrode active material layer can also be provided between the solid electrolyte layer and the negative electrode collector as needed.
[0103] An embodiment of the all-solid-state battery has been described above, but the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0104] Example
[0105] Hereinafter, the present invention will be described in more detail by way of examples, but the technical scope of the present invention is not limited to the following examples.
[0106] 《Production of positive electrode active material layer, solid electrolyte layer and test battery cell》
[0107] (Fabrication of Positive Electrode Active Material Layer)
[0108] [Comparative Example 1]
[0109] As the constituent material of the positive electrode active material layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1O2), lithium ion conductive halogen-containing sulfide solid electrolyte, namely argyrodite-type solid electrolyte (Li6PS5Cl, average particle size (D50) 0.8μm), fibrous conductive aid, namely vapor-deposited carbon fiber (VGCF), and fibrillated binder, namely polytetrafluoroethylene (PTFE). In a glove box with an argon atmosphere at a dew point below -68°C, NMC composite oxide, solid electrolyte, binder (PTFE), and fibrous conductive aid (VGCF) are weighed in a mass ratio of 78.8:15.3:2.9:3.0, mixed in an agate mortar, and further mixed and stirred using a planetary ball mill. In this way, the binder (PTFE) is fibrillated to obtain a powder composition (positive electrode mixture). After confirming that the PTFE is fibrillated and becomes fibrous, the obtained powder composition (positive electrode mixture) is supplied to the powder inlet installed in the roller press. Then, the powder composition was rolled using a roller press (conditions as shown below) to form the powder composition into a sheet to prepare the positive electrode active material layer of Comparative Example 1. The content of the binder in the positive electrode active material layer was 2.9% by mass, and the content of the conductive aid was 3.0% by mass.
[0110] (Conditions of roller press)
[0111] Roller size:
[0112] Roller speed: 1m / min
[0113] Pressure: 10kN (linear pressure: 25kN / m).
[0114] [Positive Electrode Active Material Layer of Comparative Example 2]
[0115] A positive electrode active material layer of Comparative Example 2 was obtained in the same manner as in Comparative Example 1 except that the content of the binder in the positive electrode active material layer was 3.3 mass %.
[0116] [Positive Electrode Active Material Layer of Comparative Example 3]
[0117] A positive electrode active material layer of Comparative Example 3 was prepared in the same manner as in Comparative Example 1 except that the content of the binder in the positive electrode active material layer was 0.5 mass %.
[0118] [Positive Electrode Active Material Layer of Comparative Example 4]
[0119] The positive electrode active material layer was obtained in the same manner as in Comparative Example 1, and the positive electrode active material layer was folded in half and subjected to rolling treatment using a roller press for compression twice, and the positive electrode active material layer of Comparative Example 4 was prepared in the same manner. Here, in the second and subsequent rolling treatments, the spacing between the rollers was set to less than half the thickness of the supplied powder composition for compression (the same below).
[0120] [Positive Electrode Active Material Layer of Example 1]
[0121] The positive electrode active material layer of Example 1 was produced in the same manner except that the positive electrode active material layer produced by the method of Comparative Example 4 was further folded in half and subjected to a rolling treatment by compression using a roll press twice.
[0122] [Positive Electrode Active Material Layer of Example 2]
[0123] A positive electrode active material layer was obtained in the same manner as in Comparative Example 1, and a positive electrode active material layer of Example 1 was prepared in the same manner except that the positive electrode active material layer was folded into three and subjected to a rolling treatment for compression using a roll press four times.
[0124] [Positive Electrode Active Material Layer of Example 3]
[0125] A positive electrode active material layer of Example 3 was produced in the same manner except that the positive electrode active material layer obtained by the method of Example 2 was further folded into three and subjected to a rolling treatment by compression using a roll press once.
[0126] [Positive Electrode Active Material Layer of Example 4]
[0127] The positive electrode active material layer was prepared in the same manner as in Comparative Example 1 except that the conductive aid was carbon black (CB). Next, the positive electrode active material layer was folded into three, subjected to rolling treatment using a roller press four times, and further folded into four, subjected to rolling treatment using a roller press twice, to prepare the positive electrode active material layer of Example 4.
[0128] (Fabrication of Solid Electrolyte Layer)
[0129] A lithium ion conductive halogen-containing sulfide solid electrolyte, namely, argyrodite-type solid electrolyte (Li6PS5Cl, average particle size (D50) 3μm) and polyvinylidene fluoride (PVdF) as a binder were mixed in a mass ratio of 95:5, and an appropriate amount of butyl acetate was added as a solvent, and mixed to prepare a solid electrolyte slurry. The solid electrolyte slurry prepared above was applied to one surface of a stainless steel (SUS430LX) foil (thickness 10μm) as a negative electrode collector, and dried to form a solid electrolyte layer (weight per unit area 3.7mg / cm 2, thickness after punching: 20 μm). Thus, a laminate of the solid electrolyte layer and the negative electrode collector was obtained.
[0130] (Production of test battery cells)
[0131] After the laminated body of the positive electrode collector, the positive electrode active material layer of Comparative Examples 1 to 4 and Examples 1 to 4 prepared above, the solid electrolyte layer prepared above and the negative electrode collector is overlapped in the order of positive electrode collector / positive electrode active material layer / solid electrolyte layer / negative electrode collector, it is bonded by isostatic pressing (700 MPa, 25° C., 1 minute) to obtain a laminated body of positive electrode collector / positive electrode active material layer / solid electrolyte layer / negative electrode collector. Then, the positive electrode lead and the negative electrode lead are connected to the obtained laminated body and placed inside the aluminum laminate film, and vacuum sealed to prepare the test battery cells of Comparative Examples 1 to 4 and Examples 1 to 4.
[0132] 《Evaluation of positive electrode active material layer》
[0133] (Evaluation of Orientation Ratio of Adhesive)
[0134] The cross sections of the positive electrode active material layers obtained in Comparative Examples 1 to 4 and Examples 1 to 4 were observed, and the orientation ratio of the binder in the direction perpendicular to the stacking direction (plane direction) of the test battery cells was calculated.
[0135] First, the cross-section of the positive electrode active material layer of Comparative Examples 1 to 4 and Examples 1 to 4 was formed, and the state of the configuration of the binder in the cross-section was determined using SEM-EDX. Specifically, the cross-section was observed by SEM-EDX, and the element specific to the binder (here, fluorine (F) element) was mapped to determine the state of the configuration of the binder. The SEM (scanning electron microscope) used was Regulus 8230 manufactured by Hitachi High-Tech Corporation, and the EDX (energy dispersive X-ray analyzer) used was Ultim (registered trademark) Extreme manufactured by Oxford Instruments.
[0136] Next, the obtained mapping data is introduced into an image processing device, and more than 100 adhesives are extracted from all the adhesives included in the cross-sectional observation image. Then, each of the extracted adhesives is processed as follows: Figure 4 The lengths of the vertical and horizontal sides of the rectangle inscribed in the adhesive were measured to calculate the aspect ratio (length of the horizontal side / length of the vertical side; 1 / tanθ). Then, the average value of the aspect ratios of the adhesives was calculated and set as the average value of the aspect ratios of the adhesives. The results are shown in Table 1.
[0137] Next, θ[°] was calculated from the average value (1 / tanθ) of the aspect ratio of the obtained binder, and the orientation ratio (%) of the binder was calculated based on the following formula 1. The results are shown in Table 1.
[0138] Orientation rate (%) = (1-θ / 90) × 100 ... (Formula 1)
[0139] (Evaluation of Orientation Ratio of Conductive Aid)
[0140] The cross sections of the positive electrode active material layers obtained in Comparative Examples 1 to 4 and Examples 1 to 4 were observed, and the orientation ratio of the conductive additive in the direction perpendicular to the stacking direction (plane direction) of the test battery cells was calculated.
[0141] First, the cross-section of the positive electrode active material layer of Comparative Examples 1 to 4 and Examples 1 to 4 was formed, and the state of the configuration of the binder in the cross-section was determined using SEM-EDX. Specifically, the cross-section was observed by SEM-EDX, and the element constituting the conductive auxiliary agent (here, the carbon (C) element) was mapped, and the state of the configuration of the conductive auxiliary agent was determined by the difference in the mapping result with the binder.
[0142] Next, the obtained mapping data is introduced into an image processing device, and 100 or more binders are extracted from all the binders included in the cross-sectional observation image. Then, the extracted conductive additives are each processed as follows: Figure 4 The lengths of the vertical and horizontal sides of the rectangle inscribed in the conductive aid were measured to calculate the aspect ratio (length of horizontal side / length of vertical side; 1 / tanθ). Then, the average value of the aspect ratio of each conductive aid was calculated and set as the average value of the aspect ratio of the conductive aid. The results are shown in Table 1.
[0143] Next, θ[°] was calculated from the obtained average value of the aspect ratio (1 / tanθ), and the orientation ratio (%) of the conductive additive was calculated based on the above-mentioned formula 1. The results are shown in Table 1.
[0144] (Tensile test of positive electrode active material layer)
[0145] The tensile modulus was measured using a tensile testing machine in accordance with JIS K7161:2014. As a sample, a positive electrode active material layer obtained in Comparative Examples 1 to 4 and Examples 1 to 4 was punched into a dumbbell shape. The test speed was set to 1 mm / s, and the above-mentioned surface direction was set as the tensile direction, and the test was carried out until the test piece broke. As a result, the values obtained by dividing the test results of each comparative example and example by the test result of Comparative Example 1 are shown in Table 1.
[0146] 《Evaluation of test battery cells》
[0147] (Performance evaluation of test battery cells)
[0148] The cycle durability of the test battery cells of Comparative Examples 1 to 4 and Examples 1 to 4 prepared above was evaluated by the following cycle test in a constant temperature thermostat set at 25°C using an electrochemical diagnostic apparatus (VSP-300 manufactured by BioLogic).
[0149] After full charging at 0.05C-3.1V constant current and constant voltage charging at 25°C and a cutoff current of 0.01C, 0.05C discharge was performed at a cutoff voltage of 1.1V. Then, the discharge capacity retention rate [%] of the 50th cycle was calculated as a percentage of the discharge capacity in the 50th cycle relative to the discharge capacity in the first cycle. The results shown in Table 1 are the values obtained by dividing the discharge capacity retention rates of Comparative Example 2 and Examples 1 to 4 by the discharge capacity retention rate of Comparative Example 2. It should be noted that in Comparative Examples 1, 2 and 4, a short circuit occurred before reaching the 50th cycle.
[0150] (Evaluation of Cracks in Positive Electrode Active Material Layer)
[0151] After the above cycle test, the test battery cells of Comparative Examples 1 to 4 and Examples 1 to 4 were disassembled, and the presence or absence of cracks in the positive electrode active material layer was visually checked.
[0152] [Table 1]
[0153]
[0154] Compared with Comparative Examples 1 to 4 in which the orientation ratio was less than 60%, the tensile strength of the positive electrode active material layer of Examples 1 to 4 in which the orientation ratio of the binder was 60% or more was more excellent. In addition, similarly, the test battery cells of Examples 1 to 4 showed better performance than Comparative Examples 1 to 4 in the cycle test, and no cracks were generated in the positive electrode active material layer after the cycle test.
[0155] Description of Reference Numerals
[0156] 10a stacked battery,
[0157] 11' negative electrode collector,
[0158] 11” positive electrode collector,
[0159] 13 negative electrode active material layer,
[0160] 15 positive electrode active material layer,
[0161] 17Solid electrolyte layer,
[0162] 19 single cell layers,
[0163] 21 Power generation element,
[0164] 25 negative electrode collector plate,
[0165] 27 positive electrode collector plate,
[0166] 29Laminating film,
[0167] 30 adhesives,
[0168] 110 rollers,
[0169] 200 base materials,
[0170] 210 substrate handling means,
[0171] 210a loading portion,
[0172] 210b driving unit,
[0173] H vertical edge,
[0174] W horizontal edge.
Claims
1. An all-solid-state battery, comprising: A positive electrode comprising a positive electrode active material layer containing a positive electrode active material and a binder; negative electrode; and a solid electrolyte layer, which is interposed between the positive electrode and the negative electrode and contains a solid electrolyte, The binder contained in the positive electrode active material layer has an orientation rate of 60% or more in a direction perpendicular to a stacking direction of the power generating element.
2. The all-solid-state battery according to claim 1, wherein: The orientation rate of the binder is 60% or more and 90% or less.
3. The all-solid-state battery according to claim 1, wherein: The orientation rate of the adhesive is 75% or more and 90% or less.
4. The all-solid-state battery according to any one of claims 1 to 3, wherein A content of the binder in the positive electrode active material layer is 0.6 mass % or more and 3.2 mass % or less relative to the total mass of the positive electrode active material layer.
5. The all-solid-state battery according to any one of claims 1 to 3, wherein The binder comprises a fibrous binder.
6. The all-solid-state battery according to claim 5, wherein: The fibrous binder includes one or more selected from the group consisting of polytetrafluoroethylene (PTFE), carboxymethyl cellulose, polyvinyl alcohol, polyethylene, nanofibers such as cellulose nanofibers, and Kevlar fibers.
7. The all-solid-state battery according to any one of claims 1 to 3, wherein The positive electrode active material layer further includes a conductive auxiliary agent.
8. The all-solid-state battery according to claim 7, wherein: The conductive additive contained in the positive electrode active material layer has an orientation ratio of 55% or more in a direction perpendicular to a stacking direction of the power generating element.
9. The all-solid-state battery according to claim 7, wherein: The conductive additive is in a fibrous or flat shape.
10. A method for producing a positive electrode active material layer for an all-solid-state battery, which is a method for producing a positive electrode active material layer for an all-solid-state battery according to claim 1, the method comprising the following forming steps: The electrode active material layer is obtained by supplying a powder composition containing the positive electrode active material and a binder to a roll press, and performing a rolling process on the powder composition two or more times using the roll press to form a sheet.
